The stability and accuracy analysis of automatic steering system with time delay. (September 2020) - Ye, Qing; Wang, Ruochen; Cai, Yinfeng; Chadli, M.
Abstract: The paper presents a systematic method of stability analysis for automatic steering system involving a time delay and some external disturbances. The analysis focuses on the stability of automatic steering system with increase of the time delay from zero to infinity. Firstly, the structure and dynamic model of automatic steering system are briefly introduced, and PD control algorithm is adopted to further analysis the time delay mechanism of control system of automatic steering system. Then the time delay dynamic models of automatic steering system with PD control algorithm are derived, the time delay stability interval and critical time delay of automatic steering system are calculated by using the generalized Sturm criterion method. Finally, the accuracy of critical time delay calculation by proposed method, and the stability and accuracy of automatic steering system with time delay and external disturbance are illustrated by numerical simulations. Highlights: A new structure of automatic steering system is proposed, and the dynamic models of automatic steering system with time delay are derived through the mechanism of tire structure. The critical time delay calculation method of active steering system is studied for the first time. The time delay stability interval and critical time delay of automatic steering system are calculated by using Strum model. The stability and accuracy of automatic steering system with time delay and external disturbance are illustrated by numerical simulations.